A systematic review of placental pathology in maternal diabetes mellitus. Issue 2 (February 2015) - Huynh, J.; Dawson, D.; Roberts, D.; Bentley-Lewis, R.
Abstract Introduction During a pregnancy complicated by diabetes, the human placenta undergoes a number of functional and structural pathologic changes, such as increased placental weight and increased incidence of placental lesions including villous maturational defects and fibrinoid necrosis. The pathologic findings reported have differed among studies, potentially reflecting differences in type of diabetes, study methodology, or glycemic control of study participants. Alternatively, these discrepancies may represent different biologic adaptations to distinct metabolic diseases. Methods We conducted a comprehensive review of English language citations in Pubmed and Embase using the keywords "diabetes", "placenta", AND "pathology". Abstracts were reviewed for relevance then full-text articles were reviewed in order to extract a comprehensive summary of current pathological findings associated with pregestational and gestational diabetes mellitus, as well as an understanding of the impact of glycemic control on placental pathology. Results Placental abnormalities most consistently associated with maternal diabetes are an increased incidence of villous immaturity, increased measures of angiogenesis, and increased placental weight. Conclusions The literature suggests that, despite similarities in placental abnormalities, differences in placental pathology may reflect differences in pathophysiology among different types of diabetes. Consequently, standardization of terminology used to define placental lesions is warranted. Moreover, further research is needed to investigate the impact of pathophysiology, glycemic control and clinical factors, such as infant sex, weight and race, on placental structure and function.